Effect Of Price, Location, And Promotion On Purchasing Decisions At Sam City - Febriati Sundari; Purnama Yanti Purba; Tommy Winata; Felix; William Wijaya (Institute of Computer Science (IOCS), 2021)
The research aim to test and analyze the effect of price, location, and promotion on purchasing decisions for Sam City Housing in the Mariendal Area, Medan. The phenomenon of declining purchasing decisions, housing prices that are more expensive than other companies, locations that are still difficult to reach and promotions that are not often carried out are the background of the research. Simple random sampling was used as a method for taking samples. The sample used is 113 people. Data analysis method using multiple linear regression. In partial data testing, price show positive and significant influence on purchasing decisions, location show positive and significant influence on purchasing decisions, promotion show positive and significant influence on purchasing decisions at Sam City Housing in the Mariendal Area, Medan..